(untitled) (Journal of Computational Mathematics, 2021)
We propose a hybrid smoothing-nonsmooth Newton-type algorithm for solving the P_0 linear complementarity problem (P_0-LCP) based on the techniques used in the non-smooth Newton method and smoothing Newton method. Under some assumptions, the proposed algorithm can find an exact solution of P_0-LCP in finite steps. Preliminary numerical results indicate that the proposed algorithm is promising.